Effect of Nd on the microstructure and corrosion behaviour of Mg-9Li-3Al magnesium alloy in 3.5 wt.% NaCl solution. (2019) - Dinesh, P.; Manivannan, S.; Kumaresh Babu, S.P.; Natarajan, S.
Abstract: As-cast Mg-9Li-3Al-xNd (x = 0-2.0 wt.%, with the variation of 0.5wt.%) magnesium alloys were prepared through casting in electrical induction melting furnace under a controlled inert gas atmosphere. Influences of Nd over the metallography changes and corrosion characteristics of Mg-9Li-3Al alloys have been examined by following techniques are OM, XRD, SEM and potentio-dynamic polarization (PDP) test. The results illustrate that adding Nd modifies the continuous β-Li phases into discontinuous phase by the formation of new precipitates such as Al2 Nd and Al11 Nd3 . Meanwhile, the grain sizes of Mg-9Li-3Al-xNd alloys reduced with respect to the increasing Nd content. PDP results disclose that the Nd addition reduces the corrosion current density (icorr ) of Mg-9Li-3Al alloys which can be essentially produced by grain refinemente.